2015
DOI: 10.1177/0961203314556139
|View full text |Cite
|
Sign up to set email alerts
|

T cells as a therapeutic target in SLE

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by a loss of tolerance to multiple endogenous antigens. SLE etiology remains largely unknown, despite recent insight into the immunopathogenesis of the disease. T cells are important in the development of the disease by amplifying the immune response and contributing to organ damage. Aberrant signaling, cytokine secretion and tissue homing displayed by SLE T cells have been extensively studied and the underlying pathogenic mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 121 publications
2
72
1
Order By: Relevance
“…Patients treated for class 3 lupus nephritis attained complete remission most successfully, while those with class 5 lupus nephritis were the least likely to respond (109). It is unclear whether adjunct therapies, such as those also targeting T cells, would improve response rates because T cells can contribute to B-cell activation and mediate tissue damage in SLE (158). Favorable outcomes with rituximab treatment were associated with attaining complete B-cell depletion, reconstitution of predominantly naive and immature B cells, and sustained suppression of memory B cells and plasma cells, whereas changes in anti-dsDNA antibodies did not correlate with response (159)(160)(161).…”
Section: Role In Gnmentioning
confidence: 99%
“…Patients treated for class 3 lupus nephritis attained complete remission most successfully, while those with class 5 lupus nephritis were the least likely to respond (109). It is unclear whether adjunct therapies, such as those also targeting T cells, would improve response rates because T cells can contribute to B-cell activation and mediate tissue damage in SLE (158). Favorable outcomes with rituximab treatment were associated with attaining complete B-cell depletion, reconstitution of predominantly naive and immature B cells, and sustained suppression of memory B cells and plasma cells, whereas changes in anti-dsDNA antibodies did not correlate with response (159)(160)(161).…”
Section: Role In Gnmentioning
confidence: 99%
“…It is reported that loss of the Th1/Th2 balance is related to the development of SLE 2–4. Treg cells are implicated in suppressing autoreactive effector cells and maintenance of peripheral immune tolerance 5. The role of Th17 cells in autoantibody production is contentious6 7; however, interleukin (IL)−17 was proved to promote local inflammation in the lupus kidney 8.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired IL-2 production by activated T cells is a hallmark of both murine and human SLE (4,(11)(12)(13). Previous studies have shown that CD4 + T cells from SLE patients display lower levels of CD25, the α chain of the IL-2 receptor (IL-2R), compared with healthy subjects (14)(15)(16).…”
mentioning
confidence: 99%